1977
DOI: 10.1346/ccmn.1977.0250405
|View full text |Cite
|
Sign up to set email alerts
|

Flouride Content of Clay Minerals and Argillaceous Earth Materials

Abstract: A reliable method, utilizing a fluoride ion-selective electrode, is described for the determination of fluoride in clays and shales. Interference by aluminum and iron is minimal. The reproducibility of the method is about ___5~0 at different levels of fluoride concentration.Data are presented for various clay minerals and for the <2-/~m fractions of marine and nonmarine clays and shales. Fluoride values range from 44 ppm (0.0044%) for nontronite from Colfax, WA, to 51,800 ppm (5.18%) for hectorite from Hector,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…This means that approximately 50% of the hydroxyls in the structure are substituted by fluoride (Thomas et al 1977). This is the only sample studied where the 19F MAS-NMR spectrum consisted of two lines.…”
Section: :1 Layer Silicatesmentioning
confidence: 98%
See 1 more Smart Citation
“…This means that approximately 50% of the hydroxyls in the structure are substituted by fluoride (Thomas et al 1977). This is the only sample studied where the 19F MAS-NMR spectrum consisted of two lines.…”
Section: :1 Layer Silicatesmentioning
confidence: 98%
“…Thus, structural hydroxyls in minerals can be replaced by F-either during the genesis (Thomas et al 1977) or subsequent alteration (Daniel and Hood 1975) of the mineral. The natural fluorine content of clays ranges from parts per million to a few percent.…”
Section: Introductionmentioning
confidence: 99%
“…19 In addition, Thomas et al. 20 showed that even natural hectorite have as much as 50% of its hydroxyl groups substituted with fluorine. Hence, even if fluorine played a major role in the intercalation process of CO2, one could still expect the observed behaviour to be also valid for natural hectorites.…”
Section: +mentioning
confidence: 99%
“…The similarity of both their electronegativity and radius allows this substitution in most types of layer silicates. Fluorine atoms are bonded to clay structures during their formation (Thomas et al, 1977) or by hydrothermal alteration (Daniel and Hood, 1975), but also during their synthesis in a fluoride medium (Granquist and Township, 1966;Torii and Iwasaki, 1987;Huve et al, 1991). For a long while, the determination of the fluorine content of clay minerals was difficult.…”
Section: Introductionmentioning
confidence: 99%
“…For a long while, the determination of the fluorine content of clay minerals was difficult. Thanks to the use of the fluoride-selective electrode (Frant and Ross, 1966) new data could be obtained (Thomas et al, 1977). The F content in clay minerals ranges from a few ppm in nontronite (API, Colfax, Washington) to more than 50,000 ppm in hectorite (API 34a, Hector, California) (Thomas et al, 1977).…”
Section: Introductionmentioning
confidence: 99%